Salafi, Jihadis, dan Terorisme Keagamaan; Ideologi, Fraksi dan Interpretasi Keagamaan Jihadis - Muhamad Ibtissam Han; Ismi Rahmayanti (Kopertais Wilayah I DKI Jakarta dan Banten, 2021)
This article will discuss the ideological roots of jihadists who use religious propositions for acts of violence, including terrorism. Ideologically, a group that is characterized by salafism or what is often called Wahabism, is an understanding that wants the purification of Islamic teachings by rejecting various interpretations other than referring to the Al-Qur'an, the prophet's hadith and the words of friends. Although in terms of faith, all Salafi factions have similarities, in terms of the application and actualization of the faith, salafism is divided into three factions, namely the puritan salafi, the political salafi and the jihadi salafi. Puritan salafis represent old groups who are anti-political, while class political salafi groups use politics as a means of defending their faith, especially jihadist groups who use revolution and even acts of violence in applying the principles of their creed. The main issues discussed in jihadiism include jihad, takfir, and al-walaa 'wa-l-baraa'.